Evaluation of mechanical properties of nickel-phosphorus layer/aluminum alloy sandwich-structure - Hanus, Petr; Zíta, Dušan; Zajíc, Jakub (TANGER, spol. s r.o., 2018)
Due to the reduction in production costs, not only in the automotive industry, more and more sandwich-structure parts are emerging to replace expensive, technologically complex elements such as cooling rotors in electrical installations. They are required to meet a complex set of attributes – resistance to abrasive wear, anti-corrosion requirements, and especially manufacturing costs. This article discusses and compares the mechanical properties of a critical part (cooling rotor) made as a sandwich structure of aluminum alloys and nickel-phosphorus (NiP) coatings. The specific mechanical and corrosive properties of the thin NiP film vary with the percentage of phosphorus and the heat treatment. On the other hand there is the loss of mechanical properties of aluminum alloy at the temperatures of the nickel-phosphorus cure. The aim of this article is to find the appropriate mechanical properties of this sandwich-structure part in the view of changing mechanical properties of each of the sandwich components. To obtain these properties, indentation methods and finite element methods are used.
Zjišťování (vyhodnocení) vhodných mechanických vlastností sendvičové konstrukce nikl-fosfor vrstvy a hliníkové slitiny
Keywords: indentation methods; nickel-phosphorus layer; aluminum alloy; mechanical properties; finite element methods; indentační metody; NiP; mechanické vlastnosti; metoda konečných prvků